Editorial Vol16 no1 - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to the April 2017 (Vol 16, No 1) issue of SJRCC. It is exactly 15 years since our first issue in 2002. This is an important milestone for us to celebrate. In doing so I want to pay special tribute to the founding editor, Professor Andy Kendrick and the Journal’s original publisher, the Scottish Institute of Residential Child Care (now CELCIS), for having the foresight to launch a journal specifically aimed at the residential child care community. The Journal’s home is in Scotland but it has always had a more global outlook.